Generation mechanism and influencing factors of transient overvoltage on ultra high-voltage direct current transmission - Weiwei Yao; Weiwei Yao; Jie Zhao; Jie Zhao; Jinqiu Dou; Jinqiu Dou; Youhan Deng; Youhan Deng; Yushu Li; Yushu Li; Yilin Liang; Yilin Liang; et al. (Frontiers in Energy Research, 2025)
The transient overvoltage caused by faults in ultra-high-voltage direct current (UHVDC) transmission lines and alternating current (AC) systems can adversely affect system safety and stability. This study theoretically analyzes the transient overvoltage generation mechanism caused by DC single-pole ground faults and typical fault conditions in two different cases by combining the DC line and AC system of the transmitting side. Considering the different generation mechanisms of the two transient overvoltages, the main factors affecting transient overvoltages were determined to be the DC line ground fault location, DC filter main capacitance, AC system short-circuit ratio, and DC transmission power. Finally, through a simulation of UHVDC transmission engineering, the relationship between various influencing factors and overvoltage was obtained, which can provide guidance in transmission engineering UHVDC design.